2014
DOI: 10.1007/s10603-014-9257-1
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Responses to Traditional Versus Hybrid Advertising Formats: The Moderating Role of Persuasion Knowledge

Abstract: Research on the impact of advertising on children has failed to keep pace with the rapidly changing media environment. Using an experimental approach, children's responses towards traditional (television advertisement) versus new, hybrid advertising techniques (trailer, advergame and their combination), and the moderating role of persuasion knowledge are investigated. Results show that children who played an advergame have more difficulty recalling the advertised brand than children who saw a traditional telev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 71 publications
(136 reference statements)
2
58
0
5
Order By: Relevance
“…Therefore, knowledge and understanding of advertising constitutes one dimension of literacy, but a further question relates to the extent to which children subsequently retrieve and employ such knowledge as a filter or defence against advertising (e.g. Verhellen, Oates, De Pelsmacker and Dens, 2014;Rozendaal, Lapierre, Van Reijmersdal and Buijzen, 2011;Young, 2003).…”
Section: Theoretical Background Advertising Literacy In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, knowledge and understanding of advertising constitutes one dimension of literacy, but a further question relates to the extent to which children subsequently retrieve and employ such knowledge as a filter or defence against advertising (e.g. Verhellen, Oates, De Pelsmacker and Dens, 2014;Rozendaal, Lapierre, Van Reijmersdal and Buijzen, 2011;Young, 2003).…”
Section: Theoretical Background Advertising Literacy In Childrenmentioning
confidence: 99%
“…Equally, the requirement to understand how children process and experience brands in the context of the influential role of the internet in tandem with traditional forms of advertising media has been noted in the literature (e.g. Verhellen, Oates, De Pelsmacker and Dens, 2014;Nairn, Griffin and Wicks, 2008;Moore and Rideout, 2007).…”
Section: Children's Advertising Literacy In An Online Contextmentioning
confidence: 99%
“…Nowadays, however, children are increasingly embracing non-traditional media platforms such as interactive games, social networking sites and branded websites (Vanwesenbeeck et al, 2016). These online platforms differ from traditional media in that they seek to offer children the facility for play, entertainment and immersion in the overall experience over a longer period of time (Verhellen et al, 2014). A widely expressed concern in the literature is that the embedded, interactive and entertaining capabilities of online platforms can lead to commercial messages exerting more subtle and persuasive effects on children, who also may not be fully aware of the nature and purpose of these commercial messages (Owen et al, 2013;Rozendaal et al, 2011).…”
Section: The Impact Of Marketing On Children's Well-being In a Digitamentioning
confidence: 99%
“…Instructing our patients on how food and beverage companies operate online is important, and previous studies have showed that children who recognize the persuasive intent of commercial messages are more critical towards advertisements, for instance by developing counterargumentation. 22 Clinicians can assist in deconstructing food advertisement to inform adolescents what the aim of advertising is and how manufacturers try to affect them in various ways: for example, by using an illustrative advertisement (for example, billboards, online ads) and asking the adolescents if they can identify marketing techniques in these, such as animation, filming tricks or the use of celebrities. It is also important to explain and exemplify that when the adolescents see friends share images of, for example, Coca-Cola bottles in their Instagram accounts, 12 Coca-Cola aims to make money and that the company want the adolescents to identify with their brand, to form a personal relationship.…”
Section: Recommendations For Actionmentioning
confidence: 99%